The Influence of Learning Methods and Parental Support on Students' Interest in Learning at Mts. Badrussalam Surabaya - Khasani, Dian Farda Al; Darmawan, Didit (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The learning process can run successfully if students are supported by their own interest in learning. One of the determining factors for success in learning activities is determined by interest. This means that students who are interested in learning will always pay attention to the material explained by the teacher and try to remember the lesson without being forced by anyone. In the past few decades, it is inevitable that students' interest in learning fluctuates easily. As explained above, interest in learning comes from within the students themselves, however there are external and internal factors that also influence the development of interest in learning, including learning methods and support from parents. The role of learning methods and parental support in students' interest in learning is the basic reason why this research is necessary and important to carry out. The aim of this research is to determine and analyze the significant influence of learning methods on students' interest in learning at MTs. Badrussalam Surabaya and to find out and analyze the significant influence of parental support on students' interest in learning at MTs. Badrussalam Surabaya. This research uses quantitative research with a correlational approach and data analysis techniques using multiple linear regression. Based on analysis and hypothesis testing, the results of this research show that there is a significant influence of learning methods on students' interest in learning at MTs. Badrussalam Surabaya and there is a significant influence of parental support on students' interest in learning at MTs. Badrussalam Surabaya.